Evaluation of dermoscopic findings of longitudinal melanonychia in referred patients to dermatology clinics in Guilan, Iran - Kaveh Gharaei Nejad; Hojat Eftekhari; Abbas Darjani; Narges Alizadeh; Rana Rafiei; Reyhaneh Ghadarjani; Mitra Elyasi; Negin Pour-Shahidi (Journal of Current Oncology and Medical Sciences, 2023)
Introduction: Longitudinal melanonychia (LM) is a common clinical condition that is mostly identified by the presence of longitudinal, demarcated, and pigmented bands on the nail. Different benign or malignant pathologies can present with longitudinal melanonychia. Therefore, we aimed to investigate the frequency of dermoscopic features of LM in patients with LM referred to dermatology clinics in Guilan, Iran.